A New Test of the Three Moment Capital Asset Pricing Model - Lim, Kian Guan (Institutional Knowledge at Singapore Management University, 1989)
In the 3-moment capital asset pricing model constructed by Kraus and Litzenberger (1976), systematic skewness contributes to the risk premium of an asset. Earlier tests of the Kraus-Litzenberger (K-L) model relied either on cross-sectional regressions or on the assumptions of multivariate normality. Cross-sectional regressions have measurement error problems and yield estimators that are less efficient than estimators in a multivariate approach. By developing a set of moment conditions based on the theoretical implications of the K-L model, the model can be tested using Hansen's (1982) generalized method of moments (GMM) method. The GMM method does not impose strong distributional assumptions on asset returns. The results of the tests suggest that systematic skewness is priced and that further research about the skewness model would be worthwhile.